2016
DOI: 10.1103/physrevd.94.064006
|View full text |Cite
|
Sign up to set email alerts
|

PVcriticality of logarithm-corrected dyonic charged AdS black holes

Abstract: In this paper, we consider dyonic charged AdS black hole which is holographic dual of a van der Waals fluid. We use logarithmic corrected entropy and study thermodynamics of the black hole and show that holographic picture is still valid. Critical behaviors and stability also discussed. Logarithmic corrections arises due to thermal fluctuations which are important when size of black hole be small. So, thermal fluctuations interpreted as quantum effect. It means that we can see quantum effect of a black hole wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 19 publications
2
112
0
Order By: Relevance
“…The thermal fluctuations can affect the critical behaviors of black holes. Such corrections to a dyonic charged anti-de Sitter black hole have been studied, and it has been observed that such a corrected solution also describes a van der Waals fluid [35]. It is also expected that such corrections to the solutions in AdS can be used to study the modifications to the quark-gluon plasma, and this can be done using the AdS/CFT correspondence [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal fluctuations can affect the critical behaviors of black holes. Such corrections to a dyonic charged anti-de Sitter black hole have been studied, and it has been observed that such a corrected solution also describes a van der Waals fluid [35]. It is also expected that such corrections to the solutions in AdS can be used to study the modifications to the quark-gluon plasma, and this can be done using the AdS/CFT correspondence [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Such corrections may affect the critical behaviors of black object, for example a dyonic charged anti-de Sitter black hole, which is holographic dual of a Van der Waals fluid [35], is considered in the Ref. [36] where logarithm-corrected thermodynamics is investigated with the result that holographic picture is still valid. However, the van der Waals phase transitions of charged black holes in massive gravity without any order correction is discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The string theory corrections to the area-entropy law of a back hole have been obtained, and it has been observed that such corrections are logarithmic [13][14][15][16]. The correction term obtained from the generalized uncertainty principle is also a logarithmic term [17,18].In the recent work [19], the logarithmic correction applied to the dyonic charged anti-de Sitter black hole, and holographic dual Van der waals fluid has been studied. Another kind of logarithmic correction already * Electronic address: b.pourhassan@du.ac.ir † Electronic address: f2mir@uwaterloo.ca ‡ Electronic address: capozzie@na.infn.it…”
mentioning
confidence: 99%
“…In the recent work [19], the logarithmic correction applied to the dyonic charged anti-de Sitter black hole, and holographic dual Van der waals fluid has been studied. Another kind of logarithmic correction already * Electronic address: b.pourhassan@du.ac.ir † Electronic address: f2mir@uwaterloo.ca ‡ Electronic address: capozzie@na.infn.it…”
mentioning
confidence: 99%
See 1 more Smart Citation